1984
DOI: 10.1029/tc003i001p00019
|View full text |Cite
|
Sign up to set email alerts
|

The neotectonics of the Tibetan Plateau

Abstract: Part of the continuing northward convergence between India and Eurasia is probably taken up by strike slip displacement, with Tibet as a whole moving eastward away from the collision zone and undergoing east–west extension (Molnar and Tapponnier, 1975; Ni and York, 1978). On the basis of our interpretation of Landsat images we propose that strike slip faulting occurs throughout the Tibetan plateau such that its north–south cross section is being shortened, with little contemporary folding or thrusting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…This apparent kinematic connection was integrated with the previous studies on active tectonics, our active fault survey during 2000(Tapponnier and Molnar, 1977Ni and York, 1978;Molnar and Tapponnier, 1978;Molnar and Chen, 1983;Molnar and Lyon-Caen, 1989;Rothery and Drury, 1984;Armijo et al, 1986Armijo et al, , 1989Wang et al, 1998;Deng et al, 2002;Taylor et al, 2003;Taylor and Peltzer, 2006;Wu et al, 1992Wu et al, , 2004bWu et al, , 2005bWu et al, , 2006Wu et al, , 2007Wu et al, , 2008Wu et al, , 2009, and active faults re-mapped by using satellite images, especially in the central and southern parts of Tibet ( Fig. 1) to better understand the relation of crustal movement and seismicity.…”
Section: Present-day Crustal Deformation In Tibet Inferred By Migratimentioning
confidence: 87%
See 2 more Smart Citations
“…This apparent kinematic connection was integrated with the previous studies on active tectonics, our active fault survey during 2000(Tapponnier and Molnar, 1977Ni and York, 1978;Molnar and Tapponnier, 1978;Molnar and Chen, 1983;Molnar and Lyon-Caen, 1989;Rothery and Drury, 1984;Armijo et al, 1986Armijo et al, , 1989Wang et al, 1998;Deng et al, 2002;Taylor et al, 2003;Taylor and Peltzer, 2006;Wu et al, 1992Wu et al, , 2004bWu et al, , 2005bWu et al, , 2006Wu et al, , 2007Wu et al, , 2008Wu et al, , 2009, and active faults re-mapped by using satellite images, especially in the central and southern parts of Tibet ( Fig. 1) to better understand the relation of crustal movement and seismicity.…”
Section: Present-day Crustal Deformation In Tibet Inferred By Migratimentioning
confidence: 87%
“…Previous studies, using satellite image interpretations and faultplane solution data, discovered normal faults and seven roughly north-south oriented rift systems are the most prominent active tectonic features in southern Tibet (Tapponnier and Molnar, 1977;Molnar and Tapponnier, 1978;Molnar and Chen, 1983;Molnar and Lyon-Caen, 1989;Ni and York, 1978;Rothery and Drury, 1984). Subsequently field investigations demonstrated that these active normal faults and rifts resulted from east to west crustal extension perpendicular to the India-Asia convergence (Armijo et al, 1986;Wu et al, 1992;Wu et al, 2004aWu et al, , 2006Wu et al, , 2008.…”
Section: Geological Settingmentioning
confidence: 91%
See 1 more Smart Citation
“…The strike and sense of slip of this earthquake are consistent with the regional tectonics. In response to the India-Eurasian plate collision, the plateau is moving outward to the east, and in central Tibet this movement is accommodated by extension along north-south striking normal faults and left-lateral slip along faults with a northeast-southwest strike (or their conjugates) [Rothery and Drury, 1984]. The mapped Kun Lun fault does not extend this far west, but the fact that these major earthquakes occurred just west of the mapped trace of this major strike-slip fault suggests that the fault may be a splay or extension of the Kun Lun fault system.…”
Section: Rupture Characteristics and Tectonic Implicationsmentioning
confidence: 99%
“…Among the various styles of deformation, north -south and northeast -southwest trending rift zones, which indicate generally east -west extension, are enigmatic features. They are distributed mainly in the southern and central Tibetan Plateau [Molnar and Tapponnier, 1978;Armijo et al, 1986Armijo et al, , 1989Rothery and Drury, 1984], where topography reaches high altitudes. Field observations indicate that the magnitude of this extension is small (<1%) [Armijo et al, 1986] and rifting in southern and central Tibet started about 13.5-14 Ma ago [Yin et al, 1994;Coleman and Hodges, 1995;Harrison et al, 1995;Blisniuk et al, 2001].…”
Section: Introductionmentioning
confidence: 99%